2001
DOI: 10.1111/j.1365-2966.2001.04660.x
|View full text |Cite
|
Sign up to set email alerts
|

The SuperCOSMOS Sky Survey - I. Introduction and description

Abstract: In this, the first in a series of three papers concerning the SuperCOSMOS Sky Survey (SSS), we give an introduction and user guide to the survey programme. We briefly describe other wide‐field surveys and compare them with our own. We give examples of the data, and make a comparison of the accuracies of the various image parameters available with those from the other surveys providing similar data; we show that the SSS data base and interface offer advantages over these surveys. Some science applications of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
553
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(557 citation statements)
references
References 38 publications
3
553
0
1
Order By: Relevance
“…About 1 million of the 2MASS galaxies are within its approximate completeness limit of Ks 13.9 mag (Vega). By cross-matching the 2MASS XSC sample with two other major all-sky photometric surveys (deeper than 2MASS), SuperCOSMOS scans of photographic plates (Hambly et al 2001) and mid-IR satellite data from WISE (Wright et al 2010), obtained multiwavelength information for the majority (95%) of 2MASS galaxies. This allowed further to derive photometric redshifts for these sources, by employing the empirical ANNz algorithm (Collister & Lahav 2004) trained on subsamples drawn from spectroscopic redshift surveys overlapping with 2MASS.…”
Section: The 2mass Photometric Redshift Cataloguementioning
confidence: 99%
“…About 1 million of the 2MASS galaxies are within its approximate completeness limit of Ks 13.9 mag (Vega). By cross-matching the 2MASS XSC sample with two other major all-sky photometric surveys (deeper than 2MASS), SuperCOSMOS scans of photographic plates (Hambly et al 2001) and mid-IR satellite data from WISE (Wright et al 2010), obtained multiwavelength information for the majority (95%) of 2MASS galaxies. This allowed further to derive photometric redshifts for these sources, by employing the empirical ANNz algorithm (Collister & Lahav 2004) trained on subsamples drawn from spectroscopic redshift surveys overlapping with 2MASS.…”
Section: The 2mass Photometric Redshift Cataloguementioning
confidence: 99%
“…The 2MASS sources and the UCAC3 counterparts were superimposed on the images to assess the reliability of the cross-match. Besides, we used other available astro-photometric databases, namely the Astrographic Catalogue AC2000.2 (Urban et al 1998) and the SuperCOSMOS Sky Survey (Hambly et al 2001) to verify the peculiar proper motions, and the USNO-B Catalog (Monet et al 2003) and the PPMX and PPMXL catalogues (Röser et al 2008(Röser et al , 2010 for comparison. This procedure showed that the clearly discrepant proper motions were mostly caused by errors in the measurements, mainly from centroiding errors or source confusion.…”
Section: Kinematic Groups Towards Chamaeleonmentioning
confidence: 99%
“…Figure 2 shows a comparison between our determination of proper motion and that of some literature sources. We see how good agreement is reached in all cases with 2MASS and UKIDSS measurements although some dispersion is found with the SuperCosmos Sky Survey (Hambly et al 2001a(Hambly et al , 2001b(Hambly et al , 2001c and Position and Proper Motion Extended-L catalogue (PPMXL; Roeser et al 2010) measurements. The values we obtained for the SLoWPoKES II and WDS objects are in agreement with the correspondent catalogue results, except for 2MASS J13104398+1434338 / 2MASS J13104431+1434326 pair for which no proper motion is given in the WDS catalogue.…”
Section: Proper Motionsmentioning
confidence: 69%